Zur Beitragsfinanzierung des Kurzarbeitergeldes - Leonard Münstermann (Wirtschaftsdienst, 2012)
Der Einsatz von Kurzarbeit in der Wirtschaftskrise hat dazu beigetragen, dass die Arbeitslosenquote trotz Rezession nahezu konstant geblieben ist. Dabei kam das Kurzarbeitergeld vorwiegend sozialversicherungspfl ichtig Beschäftigten größerer Betriebe zugute. Dieser Beitrag geht der Frage nach, ob eine Finanzierung aus Beitragsmitteln der Arbeitslosenversicherung angemessen ist. – – The stability of the German labour market despite a 5.1% decrease in GDP in 2009 has been described as the German job miracle. A contributing factor was the political decision to prolong the length of eligibility for short-time working benefits. Short-time working benefits are part of the unemployment insurance, which means that all employers and employees have to contribute. Nevertheless, short-time working benefits are predominantly used by large corporations in the industrial sector and their highly skilled employees. This article therefore asks whether the funding by collected contributions is justifiable or whether short-time working benefits should be paid for by taxes, if at all.
Keywords: J48; J65; 330; Lohnersatzleistungen; Sozialversicherungsfinanzierung; Deutschland